Cattle behavioral responses following castration and dehorning measured by accelerometers. - Pauly, Craig Robert (Kansas State University, 2011)
Castration and dehorning are common husbandry practices in the United States. The objective of this research was to evaluate behavioral responses to these painful procedures. Two studies were conducted using three dimensional accelerometers to measure behavioral differences in cattle following dehorning and castration. The first study evaluated the potential of different analgesics to mitigate pain following castration and dehorning compared to negative controls as judged by behavioral measures. Holstein-Fresian calves given one of three different analgesic protocols (sodium salicylate, a combination of xylazine, ketamine and butorphanol, and both treatments together) or received no analgesia. All cattle were surgically castrated and dehorned. All treatment groups spent more time lying down and less time walking in the post-surgery than pre-surgery, and significant interactions were found between treatment and time relative to surgery (P<0.05). The second study evaluated behavioral changes following castration and dehorning performed independently or concurrently when compared to a negative control (no surgery). Accelerometers recorded behavior in Holstein-Fresian calves in which differing surgical procedures were performed: castration only (CO), dehorning only (DO), castration and dehorning (CD), and no surgical procedure performed (CON). Behavioral data was measured for 6 days following surgery. Significant interactions were found between treatment and time (P<0.05) in both walking and lying behavior. Calves that were dehorned and castrated spent less time walking one day after the procedure compared to controls, but very few other behavioral differences were identified. These studies illustrate that cattle behavior changes following painful procedures such as castration and dehorning.
Keywords: Cattle; Behavior; Veterinary Medicine (0778)